Association between Early Neuroretinal Dysfunction and Peripheral Motor Unit Loss in Patients with Type 1 Diabetes Mellitus. (4th October 2018) - Picconi, Fabiana; Mataluni, Giorgia; Ziccardi, Lucia; Parravano, Mariacristina; Di Renzo, Antonio; Ylli, Dorina; Pasqualetti, Patrizio; Studer, Valeria; Chioma, Laura; Marfia, Girolama Alessandra; Frontoni, Simona
Abstract : Objectives . It has been already confirmed that retinal neurodegeneration has a predictive value in the development of microvascular alterations in diabetic retinopathy. However, no data are available on the association between neuroretinal dysfunction and peripheral motor unit loss. Our study, therefore, was aimed at investigating the hypothesis that retinal neurodegeneration could be considered an early marker of diabetic peripheral neuropathy (DPN). Methods. 20 T1DM patients with no symptoms/signs of peripheral polyneuropathy, without DR or with very mild nonproliferative DR, and 14 healthy controls (C) age- and gender-matched were enrolled. The following electrophysiological tests were performed: standard nerve conduction studies (NCS) and incremental motor unit number estimation (MUNE) from the abductor hallux (AH) and abductor digiti minimi (ADM). Neuroretinal function was studied by multifocal electroretinogram (MfERG) recordings, measuring response amplitude density (RAD) and implicit time (IT) from rings and sectors of superior (S)/inferior (I)/temporal (T)/nasal (N) macular sectors up to 10 degrees of foveal eccentricity. Results. MfERG RADs from rings and sectors were significantly reduced in T1DM (p < 0.05 ) vs. C. ADM MUNE and AH MUNE were significantly decreased in T1DM (p = 0.039 andp < 0.0001, respectively) vs. C. A positive correlation between mean MfERG RADs from the central 5 degrees of the four (S, I, T, and N) macular sectors and lower limb motor unit number (r = 0.50, p = 0.041 ;r = 0.64, p = 0.005 ;r = 0.64, p = 0.006 ; andr = 0.61, p = 0.010, respectively) was observed in T1DM patients. No abnormalities of NCS were found in any subject. Conclusions. The motor unit loss on the one hand and neuroretinal dysfunction on the other hand are already present in T1DM patients without DPN. The relationship between neuroretinal dysfunction and motor unit decline supports the hypothesis that neuroretina may represent a potential "window" to track the early neurogenic damage in diabetes.